Unidimensional scales for fears of cancer recurrence and their psychometric properties: the FCR4 and FCR7 - G. M. Humphris; E. Watson; M. Sharpe; G. Ozakinci (Health and Quality of Life Outcomes, 2018)
Abstract Background The assessment of fear of recurrence (FCR) is crucial for understanding an important psychological state in patients diagnosed and treated for cancer. The study aim was to determine psychometric details of a seven question self-report scale (FCR7) and a short form (FCR4) based upon items already used in various extensive measures of FCR. Methods Two consecutive samples of patients (breast and colorectal) were recruited from a single specialist cancer centre. The survey instrument contained the FCR7 items, Hospital Anxiety and Depression Scale (HADS), and demographic details. Clinical information was obtained from patient hospital records. Statistical analyses were performed using classical test and item response theory approaches, to demonstrate unidimensional factor structure and testing key parameters. Construct validity was inspected through nomological and theoretical prediction. Results Internal consistency was demonstrated by alpha coefficients (FCR4: 0.93 and FCR7: 0.92). Both scales (FCR7 & FCR4) were associated with the HADs subscales as predicted. Patients who experienced chemotherapy, minor aches/pains, thought avoidance of cancer and high cancer risk belief were more fearful. Detailed inspection of item responses profile provided some support for measurement properties of scales. Conclusion The internal consistency, and pattern of key associations and discriminability indices provided positive psychometric evidence for these scales. The brief measures of FCR may be considered for audit, screening or routine use in clinical service and research investigations.